An analysis of innovation performance of the Western Balkan countries and the EU selective economies group - Cvetanović Slobodan; Nedić Vladimir (Međunarodni Problemi)
First of all, the paper offers a theoretical explication of the importance of economic innovation for a country’s economic development. It further considers the metrics of the Global Innovation Index. By means of a box-plot diagram, the article explores the link between basic innovation performances (Global Innovation Index, Index Innovation Input and Index Innovation output) of the six Western Balkan countries (Albania, Bosnia and Herzegovina, Macedonia, Serbia, Croatia and Montenegro) and a group of six selected European Union economies in the neighbourhood (Austria, Greece, Bulgaria, Romania, Hungary and Slovenia). The aim is to identify the existence of extreme values between the data that reveal the key innovation performance of the two groups including the description of the basic characteristics of the performances which have been examined.